New Media In Malaysia In Projecting Collective Action - Fernandez, Kevin (Universiti Sains Malaysia, 2014)
New media has significantly lowered the cost of publication, transcending geographical boundaries making spatial and temporal impediments redundant. Due to technological advancements, new media has also become more pervasive in society and it has started to compete with traditional media. This thesis explores the relationship between the use of new media by the Lifeworld (society) and its accompanying Web 2.0 technologies, and the System (structure) in Malaysia, with a long history of regulating the press and free speech, using the Argumentative Discourse Analysis (ADA) framework. The study adopted the ‘Web Crawling’ and snowball blog-seeding method of gathering an initial list of bloggers and online activists for online and offline semi-structured interviews added with the content analysis (blogs) and secondary method for the purpose of this study. Results show that with the rise of a ‘New’ middle class, collective action through new media activists have given birth to New Social Movements such as Bersih and online activism (Hactavism) in Malaysia. Most importantly, through new media (independent newportals, blogs cybertroopers) the opposition with the assistance of coalitional capital of CSOs and CSAs in their agenda setting have employed discursive formations that have led to resistance or contentious politics (resistance of Colonisation by the System) in the context of Malaysia. These strategies and tactics of resistance politics through collective actions such as NSMs and hactavism have resulted in different policy implications by the Malaysian government.